Optimization of Chitosan Concentration on the Quality and Shelf Life of Frozen Rohu (Labeo rohita) Fillets - Faria Afrin; Md. Golam Rasul; Murshida Khan; Taslima Akter; Chunhong Yuan; A. K. M. Azad Shah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2021)
A natural product such as chitosan promotes health benefits and extends the shelf life of the processed products. Chitosan has been used as a food additive due to its antioxidant and antimicrobial activities. This study was conducted to optimize the chitosan concentration as a coating agent on the quality and shelf life of Labeo rohita fillets during frozen storage. Chitosan (CH) solutions were prepared with 0.5 %, 1 %, and 2 % (w/v) CH in 1 % (v/v) glacial acetic acid for coating application. The control (0% CH) and CH treated fish fillets were stored at -18 °C for 14 weeks and assessed for chemical (pH, thiobarbituric acid reactive substances (TBARS), total volatile basic nitrogen (TVB-N), and K-value), microbiological (aerobic plate count (APC)), and sensory properties. The pH, TBARS, and K-value of 1 % and 2 % CH treated fish fillets were acceptable up to 14th week of storage, while TVB-N value was permissible up to 12th week of  storage.  After 14th  week of  storage, the APC of control, 0.5 %, 1 %, and 2 % CH treated fillets were 7.18 log CFU/g, 5.02  log CFU/g, 4.13 log CFU/g, and 3.21 log CFU/g, respectively. The  fish  fillets treated with 1 % and 2 % CH had acceptable sensory attributes up to 12th week, while control fillets were unacceptable after the 6th week of storage. This study demonstrated that 1% CH could be used as a natural additive for keeping the quality and extending the shelf life of L. rohita fillets during frozen storage.